Prone versus Supine Position Ventilation in Adult Patients with Acute Respiratory Distress Syndrome: A Meta-Analysis of Randomized Controlled Trials - Zanfeng Cao; Zhanzheng Yang; Zijing Liang; Qingyan Cen; Zuopeng Zhang; Hengrui Liang; Rong Liu; Liangbo Zeng; Yubao Xie; Youping Wang (Emergency Medicine International)
The purpose of this meta-analysis was to compare the efficacy and safety of prone versus supine position ventilation for adult acute respiratory distress syndrome (ARDS) patients. The electronic databases of PubMed, Embase, and the Cochrane Library were systematically searched from their inception up to September 2020. The relative risks (RRs) and weighted mean differences (WMDs) with corresponding 95% confidence intervals (CIs) were employed to calculate pooled outcomes using the random-effects models. Twelve randomized controlled trials that had recruited a total of 2264 adults with ARDS were selected for the final meta-analysis. The risk of mortality in patients who received prone position ventilation was 13% lower than for those who received supine ventilation, but this effect was not statistically significant (RR: 0.87; 95% CI: 0.75–1.00; P = 0.055). There were no significant differences between prone and supine position ventilation on the duration of mechanical ventilation (WMD: −0.22; P = 0.883) or ICU stays (WMD: –0.39; P = 0.738). The pooled RRs indicate that patients who received prone position ventilation had increased incidence of pressure scores (RR: 1.23; P = 0.003), displacement of a thoracotomy tube (RR: 3.14; P = 0.047), and endotracheal tube obstruction (RR: 2.45; P = 0.001). The results indicated that prone positioning during ventilation might have a beneficial effect on mortality, though incidence of several adverse events was significantly increased for these patients.